Mechanism of Ulcerative Colitis-Aggravated Liver Fibrosis: The Activation of Hepatic Stellate Cells and TLR4 Signaling Through Gut-Liver Axis - Liu, Yu-Feng; Niu, Guo-Chao; Li, Chen-Yang; Guo, Jin-Bo; Song, Jia; Li, Hui; Zhang, Xiao-Lan (Frontiers in Physiology, 2021)
Background: The progression of liver disorders is frequently associated with inflammatory bowel disease through the gut-liver axis. However, no direct evidence showed the mechanisms of ulcerative colitis (UC) in the development of liver fibrosis per se. Thus, this study aimed to evaluate the effects of UC on liver fibrosis and its potential mechanism in the experimental model. Methods: Male C57BL/6 mice were allocated into five groups (n=10 per group) to receive either drinking water (control), 2% dextran sulfate sodium (DSS), olive oil, carbon tetrachloride (CCl4) or DSS+CCl4 for 4 cycles. Blood was collected for biochemical analysis. Colons were excised for the evaluation of colon length and morphological score. Liver, colon, and mesenteric lymph nodes (MLNs) were collected for histopathological staining, expression analysis, and bacterial translocation assay to evaluate the inflammation, fibrosis, the activation of hepatic stellate cells (HSCs), and gut barrier function. Results: DSS caused severe colitis in mice treated or treated with CCl4, as evident from the elevation of disease activity index (DAI), histological abnormalities, and increased pro-inflammatory cytokines (TNF-α, IFN-γ, and IL-17A) and. Histopathological staining revealed that DSS treatment aggravated the CCl4-induced extracellular matrix deposition, liver fibrosis, and inflammation in mice. Additionally, biochemical and expression analysis indicated the DSS treatment caused the increase of hydroxyproline and pro-inflammatory cytokines, as well as the abnormal liver function indexes in CCl4-induced mice. Gut barrier function was impaired in DSS- and DSS+CCl4-treated mice, manifesting as the increase in bacterial translocation and lipopolysaccharide level, and the reduction in tight junction proteins (occluding, claudin-1 and ZO-1) expression. Further, the activations of HSCs and TLR4 signalling pathway were observed after DSS+CCl4 treatment, presenting with the increase in expression of α-SMA, vimentin, TGF-β, collagen type Ⅰ, collagen type Ⅲ, TIMP-2, TLR4, TRAF6, and NF-κB p65, and a decrease in GFAP and MMP-2 expression. Conclusions: The present study verified that UC aggravated CCl4-induced liver injury, inflammation, and fibrosis in mice through the gut-liver axis. Gut barrier dysfunction in UC leads to bacterial translocation and elevated lipopolysaccharide, which may promote the activation of TLR4 signaling and HSCs in the liver.